The Scottish National Party transition to power - Mitchell, James 1960- (Oxford University Press, 2012)
Based on a survey of the entire membership and over 80 elite interviews, 'The Scottish National Party' provides a comprehensive account of the nature of the SNP following its election as a party of government for the first time in its 80-year history
Includes bibliographical references and index
Keywords: Schottische Nationalpartei; Scottish National Party; Nationalism / Scotland; Nationalism; Scotland